Level of compliance records of Nursing in Obstetrics and Gynecology Service National Mother Child Hospital San Bartolomé, 2012 - Gutiérrez Cahuana, Julia Virginia (2019)
Objective: To determine the level of compliance of nursing records regarding the care that is provided in theservice of Gynecology and Obstetrics HONADOMANI “San Bartolome”. Methodology: It was a study of nonexperimental, descriptive transversal. The study population consisted of a population of 87 medical records ofpatients hospitalized in the service of Gynecology Obstetrics during the second week of April of 2012, yieldinga sample of 41. A road check list was developed and applied the four nursing records (Sheet Vital Functions,Kardex, Annotations of Nursing and Water Balance Sheet) of medical records that were selected randomly.Results: It was found that the nurses of Obstetrics and Gynecology nursing notes recorded between good andvery good in 75.6 %, recorded the chart sheet between good and very good in 95.1 %, as the Kardex in 65.9 %.While the Water Balance sheet as badly recorded a 65.9 % Conclusion: Nurses ginecoobstetricia service, meetnursing records make between good and very good level in 63.4% and 7.3% recorded very bad.